Cutoffs of isokinetic strength ratio and hamstring strain prediction in professional soccer players. (20th April 2017) - Dauty, M.; Menu, P.; Fouasson‐Chailloux, A.
Abstract : Hamstring strain injuries frequently occur during professional soccer practice. Low hamstring strength represents an intrinsic modifiable risk factor but cutoffs of isokinetic knee strength ratios are controversial to predict hamstring strain in professional soccer players. We aimed to predict hamstring strain in accordance with cutoffs of isokinetic knee strength ratios. Bilateral, conventional, and functional isokinetic strength ratios were calculated in 194 professional soccer players at the beginning of 15 consecutive seasons. 36 soccer players presented a moderate hamstring strain and 158 were not injured. The different calculated isokinetic ratios were compared with the right and left limb of the uninjured population. Different usual cutoffs were tested: at 0.85 and 0.90 for the bilateral concentric and eccentric hamstring‐to‐hamstring ratio, at 0.60 and 0.47 for the conventional hamstring‐to‐quadriceps ratio and at 0.80 and 1 for the mixed hamstring‐to‐quadriceps ratio. The specific ratios for the studied population were also determined by the 10th percentile and then tested. Hamstring strain prediction was established in terms of odds ratios. No cutoff with bilateral, conventional, or functional isokinetic strength ratio was predictive of hamstring strain after univariate analysis. Specific cutoffs determined from the studied population were not more predictive. Very few injured soccer players presented values under the cutoffs at 0.47 for the conventional ratio and at 0.80 for the mixed ratio. Regardless of their values, cutoffs of isokinetic strength ratios were not predictive of hamstring injuries. The use of isokinetic cutoffs is not recommended to predict hamstring muscle strain in professional soccer players.